Predictive Functional Control With Observer (PFC-O) Design And Loading Effects Performance For A Pneumatic System - Khairuddin, Osman; Ahmad ’Athif, Mohd Faudzi; Mohd Fua'ad, Rahmat; Omer Faris, Hikmat; Koichi, Suzumori (Arab J Sci Eng, 2015)
Demand for higher accuracy and control systems is growing rapidly and becomingmore important in high-tech industries. However, precise position control of a pneumatic cylinder is very difficult to achieve due to the compressibility of air, nonlinear behavior of the air flow rate through the valves and the friction force between the cylinder and the piston of the system. The purpose of this paper was to present a model and a novel linear process control strategy to design a position controller for a real-time pneumatic system. This paper mainly analyzes the horizontal and vertical precision positioning control under loading effect for pneumatic system in real-time experiment. System identification approach is selected to obtain the plant model. Predictive Functional Control with observer (PFC-O) design is proposed as control strategy to improve tracking performance of the pneumatic system. Performance assessment of the controller was performed in MATLAB. The effectiveness of the proposed control strategy is verified through real-time experiment with the plant. The simulation and the experimental results confirm that the proposed PFC-O controller shows good control performance with various load configurations.